2022
DOI: 10.1080/14786419.2022.2089880
|View full text |Cite
|
Sign up to set email alerts
|

Role of LTB4 and nitric oxide in the gastroprotective effect of Prosthechea karwinskii leaves extract in the indomethacin-induced gastric injury in the rat

Abstract: Gastric injury is mainly described by inflammation of the gastric epithelium. Recently, our group of work demonstrated that Prosthechea karwinskii leaves extract induces both an in vitro antioxidative action, and in vivo gastroprotective effect in the rat. However, the molecules involved in the gastroprotective action by Prosthechea karwinskii are not known. Thus, the aim of this study was to determine whether Prosthechea karwinskii extract modifies anti-inflammatory and antioxidative biomarkers in an in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…LTB4 can attract and activate other white blood cells, such as neutrophils, to sites of inflammation, thereby exacerbating the inflammatory response. It has been previously reported that non-steroidal anti-inflammatory drugs such as indomethacin can cause leukocyte infiltration and increase the level of leukotriene B4 in the stomach, thereby activating inflammatory pathways to attack gastric tissue [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…LTB4 can attract and activate other white blood cells, such as neutrophils, to sites of inflammation, thereby exacerbating the inflammatory response. It has been previously reported that non-steroidal anti-inflammatory drugs such as indomethacin can cause leukocyte infiltration and increase the level of leukotriene B4 in the stomach, thereby activating inflammatory pathways to attack gastric tissue [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%